2020
DOI: 10.1029/2020gl090729
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Convective Raindrop Size Distributions in the Eyewall and Spiral Rainbands of Typhoon Lekima (2019)

Abstract: A reliable shape-slope (μ-Λ) relationship for polarimetric retrieval in tropical cyclones (TCs) is unavailable due to the lack of raindrop size distribution (RSD) measurements within the TC eyewall. This study presents an analysis of the convective RSDs in the eyewall and spiral rainbands, based on~26 hr of measurement from 17 Thies disdrometers during the landfall of Typhoon Lekima (2019) in eastern China. A μ-Λ relationship for polarimetric retrieval in the eyewall is derived, which is different from those i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 60 publications
(115 reference statements)
4
21
2
Order By: Relevance
“…Hence, we compared the D m -N w pairs with those of other TCs from the same ocean (the Pacific) (Figure 6(b)). Our D m was smaller than the results of Bao et al [41], Janapati et al [31], and Zheng et al [42], while our N w was smaller than two of the results. is is probably because the results have higher rain rates and higher concentration of large drops than Typhoon Nida in this study.…”
Section: Characteristics Of Raindrop Size Distributioncontrasting
confidence: 91%
See 2 more Smart Citations
“…Hence, we compared the D m -N w pairs with those of other TCs from the same ocean (the Pacific) (Figure 6(b)). Our D m was smaller than the results of Bao et al [41], Janapati et al [31], and Zheng et al [42], while our N w was smaller than two of the results. is is probably because the results have higher rain rates and higher concentration of large drops than Typhoon Nida in this study.…”
Section: Characteristics Of Raindrop Size Distributioncontrasting
confidence: 91%
“…e Z-R relationship is significantly distinct between before landfall and after landfall. Moreover, the Z-R relationship in this study is different from the results of Bao et al [41] and Janapati et al [31]. Moreover, the mean values of the above parameters (R, Z, D m , and lgN w ) before and after landfall are listed in Table 1.…”
Section: Characteristics Of Raindrop Size Distributioncontrasting
confidence: 90%
See 1 more Smart Citation
“…In this work, we performed numerical simulation of the wind-induced airflow pattern near the sensing area of the laser precipitation monitor (LPM), manufactured by Thies Inc. This NCG is widely used by researchers, see, e.g., [19][20][21][22], and is being progressively integrated in NWS precipitation measurement networks, thanks to its performance and relatively low cost [23].…”
Section: Introductionmentioning
confidence: 99%
“…Chen (1977), Chen and Xu (2017) analyzed the most extreme rainstorm processes of TCs throughout the history of China in which the 24-h accumulated rainfall exceeded 1,000 mm, and found that their maintenance and stagnation were the two most important conditions for the occurrence of extreme rainstorms. The extreme precipitation of TCs is associated mainly with the convective rain caused by the interaction of TC circulation and other weather systems (Bao et al, 2020). Cheng et al (2012) carried out a systematic study on the torrential rainfall associated with LTCs and revealed that the southwest monsoon transported the water vapor and unstable energy to TC Bilis (2006) via the low-level jet stream, which was highly beneficial to its maintenance and severe torrential rainfall.…”
Section: Introductionmentioning
confidence: 99%